The Effect of Principal’s Leadership Style and Teacher’s Job Satisfation towards Teacher’s Performance - Susilawati, Susilawati; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2021)
This study determined the effect of the principal's leadership style and teacher’s job satisfaction on teacher performance in public elementary schools in Sekayu District, Musi Banyuasin Regency. The research method is ex post facto with a population of 491 teachers The research sample draw using proportional random sampling in order to obtain a sample of 78 respondents. Data collection techniques using questionnaires. The data analysis technique used the t-test and the F-test. The results of this study can be concluded that there is a significant influence between the leadership style of the principal and teacher’s job satisfaction on the performance of elementary school teachers in Sekayu District, Musi Banyuasin Regency. This study provides the new insight for principals to more deeply give attention the leadership style and teacher’s job satisfaction in order to have good teacher’s performance.